2018
DOI: 10.1155/2018/4605925
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heating Value of Estonian Oil Shale by Laser-Induced Breakdown Spectroscopy

Abstract: The laser-induced breakdown spectroscopy (LIBS) combined with multivariate regression analysis of measured data were utilised for determination of the heating value and the chemical composition of pellets made from Estonian oil shale samples with different heating values. The study is the first where the oil shale heating value is determined on the basis of LIBS spectra. The method for selecting the optimal number of spectral lines for ordinary multivariate least squares regression model is presented. The corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The original LIBS spectra are often affected by various sources of interference from light scattering, instrument noise, and background [ 27 ]. Thus, conventional minimum-maximum normalization was employed to transform the original LIBS data to the range of 0–1 [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original LIBS spectra are often affected by various sources of interference from light scattering, instrument noise, and background [ 27 ]. Thus, conventional minimum-maximum normalization was employed to transform the original LIBS data to the range of 0–1 [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The original LIBS spectra are often affected by various sources of interference from light scattering, instrument noise, and background [ 27 ]. Thus, conventional minimum-maximum normalization was employed to transform the original LIBS data to the range of 0–1 [ 27 ]. The raw spectra acquired from the NIR spectrometer are often characterized by baseline shift and unwanted spectral variation produced from light scattering effects, variation in optical path length, random noise, sample matrix, and others.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent applications of LIBS to oil shale have been proposed for discrimination from limestone by Paris et al 41 and for determination of the caloric power. 42 LIBS was also used for in situ diagnosis of the products of combustion of oil-red power plants in 2002 by Corsi et al, 43 who demonstrated the possibility of performing remote LIBS analysis for the control of the emissions of fossil fueled power plants.…”
Section: Energy Industrymentioning
confidence: 99%